2021
DOI: 10.1055/s-0041-1739146
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia Predicts Adverse Events following Unicompartmental Knee Arthroplasty

Abstract: Hypoalbuminemia is a potentially modifiable risk factor associated with adverse events following total knee arthroplasty. The present study aimed to evaluate whether hypoalbuminemia similarly predisposes to adverse events following unicompartmental knee arthroplasty (UKA). Patients who underwent UKA during 2006–2018 were identified through the American College of Surgeons National Surgical Quality Improvement Program. Only patients with preoperative serum albumin concentration were included. Outcomes were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In studies of hip or knee joint arthroplasty, researchers have found patients suffering preoperative hypoalbuminemia had a 1.9 to 2.0-fold increased risk of any postoperative adverse events and 4-fold increased risk of blood transfusion, respectively. 27 , 28 Seong-Eun et al 29 retrospectively analyzed 519 elderly patients with hip fracture and found that the incidence of preoperative malnutrition in patients with aspiration pneumonia was significantly higher than that in the control group (36.8% vs 9.1%). Toshihiro et al 30 investigated 426 elderly patients undergoing surgery for hip fracture and found postoperative hypoalbuminemia was associated with 5.8-fold increased risk of postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of hip or knee joint arthroplasty, researchers have found patients suffering preoperative hypoalbuminemia had a 1.9 to 2.0-fold increased risk of any postoperative adverse events and 4-fold increased risk of blood transfusion, respectively. 27 , 28 Seong-Eun et al 29 retrospectively analyzed 519 elderly patients with hip fracture and found that the incidence of preoperative malnutrition in patients with aspiration pneumonia was significantly higher than that in the control group (36.8% vs 9.1%). Toshihiro et al 30 investigated 426 elderly patients undergoing surgery for hip fracture and found postoperative hypoalbuminemia was associated with 5.8-fold increased risk of postoperative pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a range of study found that preoperative intravenous iron treatment would significantly increase hemoglobin level ( 34 ) and reduce allogeneic transfusion ( 35 ) in non-anemic patients with iron deficiency undergoing cardiac surgery, supporting our findings about the impact of iron deficiency on non-anemic patients. In addition, another indicator that can be corrected preoperatively was hypoalbuminemia, which was reported as a risk factor of transfusion in other kinds of surgeries ( 36 , 37 ). Of note, diabetes was not included in the machine learning model, while high HbA1c was adopted as a risk factor.…”
Section: Discussionmentioning
confidence: 99%